The Role of Organizational Culture in Implementing Knowledge Management in Organizations: An Analytical Study - Al-Fazari, Arif Khamis (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aims to focus on the role of organizational culture in implementing knowledge management in organizations. The study explores how shared values, beliefs, and behaviors within the organization influence the organization's ability to organize, direct, and utilize knowledge. Additionally, the study elucidates how organizational culture can be a critical factor in the success of knowledge management strategies. It highlights how fostering a culture of learning, innovation, and knowledge exchange within the organization can lead to overall organizational performance improvement. Furthermore, the study reviews examples of tools and techniques that can be used to build and enhance a supportive organizational culture for knowledge management. The study also emphasizes the importance of incorporating aspects of organizational culture into human resource development strategies and shaping institutional policies and procedures. Overall, the study enhances understanding of how organizational culture impacts the implementation and utilization of knowledge management in organizational settings.
Keywords: Organizational culture; Knowledge management; Organizations